Corporate Data Responsibility - Sarfaty, Galit A. (Big Data and Armed Conflict: Legal Issues Above and Below the Armed Conflict Threshold, 2023)
This is an accepted manuscript of a book chapter in the edited volume: Big Data and Armed Conflict: Legal Issues Above and Below the Armed Conflict Threshold
This file is under embargo and will become available on 2024-12-14

Chapter 1, Introduction to contract law and theory - DiMatteo, Larry A. (Principles of Contract Law and Theory, 2023)
This chapter provides background information on the evolution of the common law of contracts. It begins with a short history of the evolution of the common law in England including the roles played by the Roman Catholic Church, the development of a dual court system—one in law and the other in equity, the transition from absolute monarchy to a parliamentary form of government, the creation and restrictiveness of the English writ system, the common law’s reception in America, and the building of a general law of contract in the nineteenth century. It explains the historical differences between law and equity, along with the fusion of the two into a single court system. It also discusses the justifications given for contract law and its role in society. It describes the different perspectives of written or formal law, theory, and practice, and importantly, the difference between law in the books versus law in action. Finally, it explains the differences between rules, principles, and standards, and the boundaries of contract relative to other areas including tort and unjust enrichment.

Chapter 11, First principles in transportation law and policy - Levine, Jonathan; Shill, Gregory H. (A Research Agenda for US Land Use and Planning Law, 2023)
The main purpose of transportation is connecting people to destinations they value. This seemingly banal statement would, if taken seriously in policymaking, upend transportation and land use planning. Today, planning agencies rely on key performance indicators (KPIs) to measure outcomes. While ostensibly neutral and technical, these measurements in fact imply policy judgments and drive legal consequences. They operate both as a shield against litigation and as a sword to justify new projects. But the way KPIs are set up reflects confusion about basic purposes. They are used to plan and evaluate based not on the ability to reach anything but rather simply to accelerate the speed of traveling. We seek to anchor transportation policy discussion in first principles. The shift we propose is mode agnostic in that it is relevant to all means of transportation. Even so, shifting from a goal of speed to one of reachability would be a leap. We believe such a shift suggests important open questions regarding the barriers to reform and we engage a few of them.

Introduction: International Adjudication and the Legacy of the Mixed Arbitral Tribunals - Ruiz Fabri, Hélène (The Mixed Arbitral Tribunals, 1919–1939: An Experiment in the International Adjudication of Private Rights, 2023)
This introduction provides the reader with a general characterization of the 39 Mixed Arbitral Tribunals (MATs) created by the 1919-1923 peace treaties to address disputes between private persons and between private persons and states as a result of the First World War. Noting that the rich literature published on the MATs was followed by near-silence after 1945, it mentions the numerous questions that they still raise today, before explaining how the various contributions to the book edited by the authors address them.

Requisitos para la prestación de servicios de financiación participativa tras la situación generada por la Covid-19 - López Ortega, Raquel (El derecho mercantil y la pandemia: algunos problemas del pasado, la crisis coyuntural y las perspectivas futuras: libro homenaje a Agustín Madrid Parra, 2023)
El texto completo del libro en que se incluye este capítulo puede descargarse de: https://www.colexopenaccess.com/libros/derecho-mercantil-pandemia-problemas-pasado-crisis-coyuntural-perspectivas-futuras-5016
Accepted: 2024-06-25T10:48:18Z

La mesure des sanctions en nature - Maire, Guillaume (Mesure(s) et droit, 2023)